The Strathclyde Inventory: Development of a Brief Instrument for Assessing Outcome in Counseling According to Rogers' Concept of the Fully Functioning Person. (3rd July 2022) - Stephen, Susan; Elliott, Robert
Abstract: The Strathclyde Inventory is a self-report instrument assessing Rogers' concept of the fully functioning person. Using data collected from a UK-based counseling service, we investigated its validity for use as an outcome measure, and produced a 12-item brief version that maintained fit to the Rasch model and construct representation.